Analysis of Waqf Management in The Context of Islamic Finance: A Case Study on Cash Waqf in Indonesia - Faujiah, Ani (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2025)
This study analyzes the management of cash waqf in the context of Islamic finance in Indonesia. Using a case study method, the research evaluates the effectiveness of cash waqf management and the challenges faced in its implementation. The findings indicate that cash waqf has significant potential in supporting the economic development of the Muslim community. However, challenges remain in terms of regulation, transparency, and public literacy. Therefore, strengthening governance strategies is necessary to optimize the benefits of cash waqf. The study implies the need for regulatory improvements and increased public awareness regarding cash waqf. The recommendations include fostering collaboration between the government, Islamic financial institutions, and the public to enhance the effectiveness of cash waqf management.